2000
DOI: 10.1038/sj.onc.1203455
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations of the MET oncogene are selected during metastatic spread of human HNSC carcinomas

Abstract: A metastatic cancer develops by accumulation of mutations in genes that control growth, survival and spreading. The latter genes have not yet been identi®ed. In lymph node metastases of head and neck squamous cell carcinomas (HNSCC), we found mutations in the MET oncogene, which encodes the tyrosine kinase receptor for Scatter Factor, a cytokine that stimulates epithelial cell motility and invasiveness during embryogenesis and tissue remodeling. We identi®ed two somatic mutations: the Y1230C, known as a MET ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
233
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 303 publications
(240 citation statements)
references
References 37 publications
5
233
2
Order By: Relevance
“…This analysis not only explains the observed selectivity but also suggests that, aside from MET, no human kinase can be potently inhibited by SGX523. Also, these results, combined with the observations that MET catalytic activity tolerates mutation of Tyr 1248 and that mutations affecting this position have been identified in human tumors (28)(29)(30), suggest that missense mutation at codon 1,248 in the MET gene is a likely mechanism of resistance to inhibitors of the SGX523 class.…”
Section: Discussionmentioning
confidence: 76%
“…This analysis not only explains the observed selectivity but also suggests that, aside from MET, no human kinase can be potently inhibited by SGX523. Also, these results, combined with the observations that MET catalytic activity tolerates mutation of Tyr 1248 and that mutations affecting this position have been identified in human tumors (28)(29)(30), suggest that missense mutation at codon 1,248 in the MET gene is a likely mechanism of resistance to inhibitors of the SGX523 class.…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that the continuous expression of this oncogene, even in advanced phases of tumor progression, is so critical that gene amplification confers a selective advantage and it is thus stably acquired. Moreover, it has been shown that MET activating mutations, preferentially driving pathways responsible for promoting invasion and protection from apoptosis, are specifically selected during metastasis, in humans (Di Renzo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The Met receptor is expressed mainly in epithelial cells (Stoker et al, 1987;Di Renzo et al, 1991), but it has also been identi®ed in endothelial cells (Bussolino et al, 1992;Grant et al, 1993), in myoblasts (Anastasi et al, 1997), in cells of the hematopoietic system (Galimi et al, 1994;Nishino et al, 1995) and in spinal motor neurons (Ebens et al, 1996). Inappropriate activation of the HGF/Met pathway has been implicated in the onset and progression of a number of tumors and has been shown to promote the metastatic spread of neoplastic cells (Di Renzo et al, 1991Vande Woude et al, 1997;Giordano et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate activation of the HGF/Met pathway has been implicated in the onset and progression of a number of tumors and has been shown to promote the metastatic spread of neoplastic cells (Di Renzo et al, 1991Vande Woude et al, 1997;Giordano et al, 1997). A more direct link between Met and cancer has been provided by the identi®cation of point mutations in the MET proto-oncogene in hereditary and sporadic papillary renal carcinomas (PRC mutations) .…”
Section: Introductionmentioning
confidence: 99%